Microstructure and performance optimisation of stainless steel formed by laser additive manufacturing. Issue 12 (12th August 2016) - Li, J.; Deng, D.; Hou, X.; Wang, X.; Ma, G.; Wu, D.; Zhang, G.
Abstract : In the present study, laser engineered net shaping technology was successfully utilised to fabricate 316L stainless steel bulk specimens using unidirectional scanning path and weaving scanning path. Influence of scanning path and post-heat treatment on microstructural and mechanical properties of the as-deposited builds has been investigated. The results show that scanning paths have a significant impact on the grain morphology evolution. Consequently, the as-made samples by different scanning strategies show a great difference in the mechanical properties. Furthermore, the experimental results also demonstrate that post-heat treatment is an essential step in further optimising microstructure and improving mechanical properties.